Acute Psychosocial Stress Reactivity and Risky Decision-making in Gambling Disorder - Arshad, Fiza (My University, 2018)
Gambling activates the hypothalamic-pituitary-adrenal and sympathoadrenal medullary (SAM) axes as evidenced by increased levels of cortisol in recreational gamblers, and in norepinephrine in problem gamblers. Further, Gambling Disorder (GD), the first non-substance related disorder in the DSM-V, is linked with stress-related conditions and psychiatric disorders. Few studies investigate interactions between stress reactivity and decision-making in GD; therefore, this study explored the effects of acute psychosocial stress induction on risky decision-making. Twenty-eight healthy control participants (HC) and 38 individuals with GD completed the Balloon Analogue Risk-taking Task (BART) and Iowa Gambling Task (IGT) following a stressor. Saliva samples, used to assess biomarkers cortisol and α-amylase, and gambling urge measures were collected at baseline, post-stressor and post-task. Results show stressor-induced increase in self-reported mood disturbance in the HC group from baseline, but not in the GD group. Stressor-induced cortisol reactivity, however, did not differ between or within groups. Unexpectedly, the stressed GD group showed reduced α-amylase reactivity following the stressor, and this decrease was significantly greater relative to the stressed HC group. The stressed GD group also made significantly less risky choices on the BART, relative to the non-stressed GD group. Further, increased α-amylase reactivity correlated with increased risky decision-making (blocks 4 and 5) on the IGT in this group. The GD group did not report stressor-induced changes in gambling urges. Overall, the differential effects of acute stress in GD is indicative of altered SAM function, possibly a result of norepinephrinergic dysfunction, that may be suggestive of changes in risk/reward appraisal and dysregulated motivational processes.